Peningkatan Hasil Belajar IPS Tentang Kerjasama ASEAN Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Talking Stick Pada Peserta Didik Kelas VI - Darniarsih Darniarsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to determine the application of the Talking Stick Type Cooperative Learning Model to student learning outcomes. Improvements to this learning were carried out for class VI students in Social Sciences (IPS) subjects on ASEAN Cooperation material. The subjects for this research were 37 students, consisting of 16 male students and 21 female students. After carrying out research on improvements to this learning, it turns out that the Talking Stick Learning Model can improve student learning outcomes, this is proven by an increase in the average score from pre-cycle, cycle I and cycle II. In the pre-cycle, only 11 students passed the KKM or (30%). In the first cycle, 29 students passed the KKM or (78%). Meanwhile, learning is said to be successful if 85% of students can reach the KKM. Therefore, cycle II learning was carried out and the result was that 32 students or (86%) were able to achieve the desired KKM.